Preanalytical factors affecting the plasma and serum levels of circulating microRNAs - E. A. Sotnikova; A. V. Kiseleva; A. N. Meshkov (Кардиоваскулярная терапия и профилактика)
Circulating microribonucleic acids (microRNAs) are promising biomarkers of various diseases, but their clinical laboratory use requires highly sensitive, reproducible, reliable and sustainable methods for their accurate plasma and serum quantification. The preanalytical phase of studies conducted using biospecimens consists of their collection, processing, storage and transportation. Preanalytical conditions remain the main distorting factors in microRNA studies, and standardization of these conditions, carried out in biobanks, can improve the reproducibility of results and their comparison. The review aim is to consider the main contemporary original studies on preanalytical factors, which are an important source of variability in studies on circulating microRNAs at the stages from blood collection to plasma or serum production.